European Bioanalysis Forum: recommendation for dealing with internal standard variability. (October 2014) - White, Stephen; Adcock, Neil; Elbast, Walid; Hiller, Jim; Knutsson, Magnus; Lausecker, Berthold; Long, Jeff; McDougall, Stuart; Salavert, Fabrice; Sangster, Timothy; Verhaeghe, Tom; Amsterdam, Peter van
Adequate monitoring of internal standard (IS) response across an analytical run and identification of anomalies is now a common expectation. However, the means to conduct this assessment in an appropriate manner is unclear and differs widely between laboratories. A European Bioanalysis Forum (EBF) topic team was formed to survey current practices within European Bioanalysis Forum member companies and to recommend a best practice approach for dealing with IS response variability.